2017
DOI: 10.1007/s12010-017-2552-y
|View full text |Cite
|
Sign up to set email alerts
|

V79 Fibroblasts Are Protected Against Reactive Oxygen Species by Flax Fabric

Abstract: Chinese hamster pulmonary fibroblasts (V79 cells) pre-treated with flax fabrics derived from non-modified or genetically engineered flax fibres and treated with HO revealed a markedly lower level of intracellular reactive oxygen species (ROS) than control, non-pre-treated cells. The fabrics were prepared from fibres derived from two kinds of transgenic plants: W92 plants, which overproduce flavonoids, and M type plants, which produce hydroxybutyrate polymer in their vascular bundles and thus in fibres. Incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…More recent research studies have carefully evaluated the efficacy of linen dressings to accelerate the healing process. Generally, the studies have proven the efficacy of using linen or flax oil to promote wound healing [ 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. There exist some conflicting studies that have not shown much beneficial effect [ 102 , 103 ] and a concern of specific preparations of linen that may induce dermal irritation [ 99 ].…”
Section: Wound Healingmentioning
confidence: 99%
“…More recent research studies have carefully evaluated the efficacy of linen dressings to accelerate the healing process. Generally, the studies have proven the efficacy of using linen or flax oil to promote wound healing [ 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. There exist some conflicting studies that have not shown much beneficial effect [ 102 , 103 ] and a concern of specific preparations of linen that may induce dermal irritation [ 99 ].…”
Section: Wound Healingmentioning
confidence: 99%
“…Moreover, ligninrich enzyme lignin (LREL) activated dendritic cells via receptor protein, TLR4, and enhanced expression of CD86, IL-12p40, and TNF-α in dendritic cells [5]. However, the structure-function relationship for the activity has not been clearly elucidated, especially at the cellular process and molecular levels, has not been clearly elucidated [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the biological and pharmacological effects of the plant-derived lignin fractions with detailed structural data, we extracted lignin by applying microwave acid-catalyzed solvolysis of softwood and hardwood and subsequent organic solvent extraction [12, 13, 14]. Microwave solvolysis in hydrophobic solvents containing alcohol and acids decomposes lignin selectively to give lignin oligomers and monomers without condensation reactions of lignin units due to trapping of unstable enol ether intermediates by the alcohol [10, 11]. The reaction products retained higher amount of native lignin interunit linkages than those obtained with acidolysis, sulfite cooking, kraft pulping and alkaline treatment under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the fibre itself was also changed. The raw materials from transgenic plants with overproduction of PHB also exhibit a number of biomedical properties [ 33 , 34 , 35 , 36 ]. It can be speculated that the observed metabolic changes in flax overproducing PHB, as well as its pro-health properties, could be caused by the activity of 3-HB.…”
Section: Introductionmentioning
confidence: 99%